(3GdJYQa aj GdCUdjf hGdJUhas - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s ((3ecI GdecQeI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG ddEYJbGO hGdYed HCUhd haQhY Ojfg Gdbhje hHYO agPg fHPI ai GdCUdjf hGdJUha , CHOYgG eG MSf GdLeY hGdJUQa s
(3BNQgG (B:s
(3bGdhG Gddge EdG ef QRb bdHkG SdjekG efgG adG jcda HTF ef Pdc dCf ehdGg EeJf Ydjg hGdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi dhdG Gf gOGfG Gddg hGddg SHMGfg hJYGdi CYde s
(3bhHdJ eY GdCUds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B152s
Keywords: (3GdeYGQa GdYGeIs